An empirical investigation on the required ICT competency readiness towards the digital economy in Thailand - Bhuvanij, Kriengkrai; Kasemsan, M. L. Kulthon; Praneetpolgrang, Prasong (2015)
This research addresses on the Thailand ICT readiness towards the Digital Economy which ICT HR competency will be a key factor to drive the country achieve the goal.The in-depth interview with the experts in the 5 areas, such as academic, ICT service/industry, business, government and foreign investment sectors, specifies the required competencies which consist of not only knowledge and skills but also attitudes which are the important part.From the study, the ICT competencies in the proposed ICT HR Competency Development Model are required by the 5 key sectors while the specific ICT competencies which are important to each sector are also explored.The results of this research will help prepare ICT workforce to drive Thailand to be ready for the Knowledge-based Economy.